Lei de Diretrizes e Bases:um caminho a percorrer entre a teoria e a prática - Anna, Mireili Lúcia de Sant (2008)
This dissertation aims to sharpen the difference between theory and practice related to the Brazilian education law, which is called Lei de Diretrizes e Bases . The research was developed among university teachers and it has the aim to sharpen how extensive the distance between theory and practice is when we consider teacher s everyday lives. According to the overwhelming majority of interviewees the Brazilian law for education is an exemplary law, however, many of them also declared that there are some difficults to comply with all law s articles. As far as law conception and its connotations are concerned, the research shows on its first two chapters a historical and social analyse related to the creation of the present Brazilian Education Law (LDB). Under the guise of conclusion, it was proved the initial idea, there is to say, the distance between theory and practice about themes which are related to Brazilian Education Law is so extensive as the thought diversities that we can find in a typical education environment.(AU)